2017
DOI: 10.1177/0300060517731683
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pinning in patients with slipped capital femoral epiphysis: risk factors associated with avascular necrosis, chondrolysis, and femoral impingement

Abstract: ObjectiveThis study aimed to assess the principal risk factors that could lead to the most common long-term complications of slipped capital femoral epiphysis, such as avascular necrosis, chondrolysis, and hip impingement.MethodsWe conducted a single-centre, retrospective study and evaluated patients (70 patients, 81 hips) who were treated for slipped capital femoral epiphysis from 2010 to 2015 and who underwent pinning. We measured the severity of displacement radiologically using the Southwick angle. Postope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
5
0
4
Order By: Relevance
“…Un resultado sorprendente fue que en promedio los DEFP estables estaban menos desplazados, pero los pacientes con DEFP inestables tuvieron mejores resultados de calidad de vida mediante iHOT-12. Además, los DEFP estables desarrollaron mayor proporción de PFA, lo que contrasta con lo informado tanto por Ulici y colaboradores, como por Lang y colaboradores (9) . A pesar de esto, los pacientes con PFA tuvieron un iHOT-12 promedio de 62, muy superior al observado en el estudio de Sansone y colaboradores, donde el iHOT-12 preoperatorio a una artroscopia de cadera por PFA era en promedio de 43 (19) .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Un resultado sorprendente fue que en promedio los DEFP estables estaban menos desplazados, pero los pacientes con DEFP inestables tuvieron mejores resultados de calidad de vida mediante iHOT-12. Además, los DEFP estables desarrollaron mayor proporción de PFA, lo que contrasta con lo informado tanto por Ulici y colaboradores, como por Lang y colaboradores (9) . A pesar de esto, los pacientes con PFA tuvieron un iHOT-12 promedio de 62, muy superior al observado en el estudio de Sansone y colaboradores, donde el iHOT-12 preoperatorio a una artroscopia de cadera por PFA era en promedio de 43 (19) .…”
Section: Discussionunclassified
“…Definimos síndrome de pinzamiento femoroacetabular cuando el paciente presentó dolor de cadera (TestPFA+) y ángulo alfa >55º (deformidad tipo CAM) (27) . Al espacio femoroacetabular menor de 3 mm o ms del 50% de reducción del espacio articular lo definimos condrólisis (9) . Para definir NAV, utilizamos la clasificación radiológica de Ficat teniendo en cuenta la destrucción epifisaria, con estadios I a IV (28) .…”
Section: Examen Radiológicounclassified
See 1 more Smart Citation
“…These classifications have an impact on the choice of the therapeutic modality and the prognosis ( Table 3). Chronic evolution, unstable form, severe displacement are independent factors of poor prognosis in terms of Avascular necrosis (AVN) [21], chondrolysis, osteoarthritis or FAI.…”
Section: A B Cmentioning
confidence: 99%
“…The degree of slip severity has been significantly correlated with delays in diagnosis in several studies [1,2,5,7,9,13,44]. A higher slip severity increases the likelihood of premature osteoarthritis and additional surgeries (e.g., osteotomies, and in some cases total hip replacements), whereas a patient diagnosed with a mild slip typically has a better outcome [2,[45][46][47][48]. Furthermore, a study from Fedorak et al (2018) showed a direct association between a longer time from symptom onset to diagnosis and a greater chance of more invasive surgery [1].…”
Section: Introductionmentioning
confidence: 99%